Retrograde headless compression screw fixation of olecranon stress fractures in throwing athletes: a novel technique - Richard M. Michelin, DO; Isaac Manuputy, BS; Brian M. Schulz, MD; Mark Schultzel, MD; Brian K. Lee, MD; John M. Itamura, MD (JSES International, 2024)
Background: An olecranon stress fracture (OSF) is a rare injury most commonly seen in high-level overhead throwing athletes with no clear consensus on surgical treatment. The most common surgical treatment described in the literature is cannulated screw fixation but there have been high rates of reported hardware irritation and need for subsequent hardware removal. Hypothesis/Purpose: This study describes a novel surgical technique in the treatment of OSFs in high-level throwing athletes using retrograde headless compression screws. We hypothesized that patients would have excellent outcomes and decreased rates of hardware irritation postoperatively. Methods: A retrospective review of competitive-level throwing athletes who sustained OSFs that were treated operatively using a novel technique using retrograde cannulated headless compression screws to avoid disruption of the triceps tendon. Postoperative outcome measures obtained included the Disabilities of the Arm, Shoulder and Hand score, Mayo Elbow Performance Score, Simple Elbow Test score, Single Assessment Numerical Evaluation score, Visual Analog Scale, arch of motion, and time to return to sport as well as level returned to. Radiographs were obtained routinely at 2-week, 6-week, 12-week, 6-month, 1-year, and 2-year follow-up. Results: Five of 5 patients who met inclusion criteria were available for final follow-up. Mean age at time of surgery was 20 years (range 17-24). Mean follow-up was 17 months (range 4-33). All patients were baseball players, 4 of which were pitchers and 1 position player. All patients were able to return to sport at the same level or higher at a mean of 5.8 months (range 3-8). Postoperatively, mean arch of motion was 138°, Visual Analog Scale score was 0, Single Assessment Numerical Evaluation score was 90, Disabilities of the Arm, Shoulder and Hand score was 2.0, Mayo Elbow Performance Score was 100, and Simple Elbow Test score was 12. There was no incidence of hardware removal. Conclusion: This study presents a novel surgical technique in the treatment of OSFs in high-level throwing athletes. The results presented demonstrate that this technique is safe and effective for getting athletes back to play quickly without any complications of hardware irritation which has previously shown to be a significant problem in prior literature.